Green Human Resource Management and Environmental Performance: Mediating Role of Employee Green Behavior and Moderating Role of Green Innovation Culture - Paul, Ripon Kumar; Karmoker, Kajol; Islam, Md Anamul; Roy, Brito; Azam, Md Shah (Indonesian Journal of Sustainability Accounting and Management, 2026)
Drawing on ability-motivation-opportunity (AMO) and resource-based view (RBV) theory, this study examines the impact of green human resource management (GHRM) on the environmental performance (EP) of star-rated hotels in Bangladesh. Additionally, the study explores the mediating role of employee green behavior (EGB) and the moderating role of green innovation culture (GIC) on the linkage between GHRM practices and EP. Based on the positivism paradigm, a quantitative approach was used for testing the study hypotheses. Data were collected from 400 employees working in the star-rated hotels of Bangladesh and analyzed through partial least squares structural equation modeling (PLS-SEM). The findings revealed that GHRM practices have a substantial positive impact on EP, and EGB mediates the effect of GHRM on EP. Moreover, the study found that GIC strengthens the association between GHRM and EP. This study contributes to the existing literature by revealing that the EP of hotels can not only be improved directly by GHRM but also through EGB and GIC. The outcomes deliver fundamental knowledge for hotel managers and policymakers striving to enhance environmental performance in line with sustainable development goals.